Around the ocean in 80 fish & other sea life - Scales, Helen (Laurence King Publishing, 2023)
"Dive beneath the waves to meet 80 of the ocean's strangest and most surprising inhabitants. This beautifully illustrated aquatic world tour tells the fascinating stories of beguiling sea creatures and their ingenious feats of survival - from producing anti-freeze to enduring boiling temperatures - revealing the ways in which these seemingly remote creatures have shapes our own lives, whether through medicine, culture or folklore."--Publisher.